Traumatic Lumbosacral Dislocation Treated with Posterior Lumbar Interbody Fusion Using Intersomatic Cages - Katsuhiro Tofuku; Hiroaki Koga; Kazunori Yone; Setsuro Komiya (Case Reports in Medicine)
A 35-year-old man was struck by a car on his right side and presented with paraparesis of both lower extremities. Radiographic examination revealed multiple transverse process fractures and anterior displacement of L5 on S1. Computed tomography revealed a bilateral anterior facet dislocation of the fifth lumbar vertebra on the sacrum. MRI showed rupture of the posterior ligamentous complex. A posterior lumbar interbody fusion using two intersomatic cages and pedicle screw instrumentation and posterior fusion were performed. Although no major disc lesion was found at the level of L5-S1 on preoperative MRI, a severely collapsed L5-S1 disc was found intraoperatively. Two years after surgery, the patient was asymptomatic with normal neurological findings, and has resumed normal activity. We believe that lumbosacral dislocation can be considered a three-column injury with an L5-S1 disc lesion, and, therefore, requires a solid circumferential segmental arthrodesis to improve fusion rate.